The Human Dermis as a Target of Nanoparticles for Treating Skin Conditions - Javier Salazar; Thais Carmona; Flavia C. Zacconi; Diego Venegas-Yazigi; Claudio Cabello-Verrugio; Won Il Choi; Cristian Vilos (MDPI AG, 2022)
Skin has a preventive role against any damage raised by harmful microorganisms and physical and chemical assaults from the external environment that could affect the body's internal organs. Dermis represents the main section of the skin, and its contribution to skin physiology is critical due to its diverse cellularity, vasculature, and release of molecular mediators involved in the extracellular matrix maintenance and modulation of the immune response. Skin structure and complexity limit the transport of substances, promoting the study of different types of nanoparticles that penetrate the skin layers under different mechanisms intended for skin illness treatments and dermo-cosmetic applications. In this work, we present a detailed morphological description of the dermis in terms of its structures and resident cells. Furthermore, we analyze the role of the dermis in regulating skin homeostasis and its alterations in pathophysiological conditions, highlighting its potential as a therapeutic target. Additionally, we describe the use of nanoparticles for skin illness treatments focused on dermis release and promote the use of metal-organic frameworks (MOFs) as an integrative strategy for skin treatments.